Investigation of nanosecond and femtosecond pulsed laser deposition and application of some metal nanoparticle films - Mirza, Inam (Trinity College (Dublin, Ireland). School of Physics, 2012)
Pulsed laser deposition (PLD) is a convenient and flexible technique which can be applied to all elemental and compound solids. In conventional PLD a nanosecond (ns) laser is used to ablate the surface of a solid target and a small amount of material expands rapidly from the target as an ionised vapour plume. Condensation of the plume on a non-wetting substrate, together with surface diffusion, leads to the formation of a nanoparticle film; the thickness is controlled by the number of laser pulses. On the other hand with femtosecond (fs) laser irradiation, very rapid heating leads to nanoscale fragmentation of a small amount of target material. Nanoparticles are expelled from the target and can be captured on a substrate. In the present work we have studied the ns- and fs-PLD of some noble and transition metals in vacuum for laser fluence well above the ablation threshold (-1.5 J cm -2). A range of techniques such as Langmuir ion probe, the time and space resolved fast imaging and optical emission spectroscopy and electron microscopy was applied to characterize the laser ablation plumes and to study the morphology of nanoparticle films.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin.